(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2013)
The F4 lines of eggplant derived from the crosses of Dohazari G x BAU Begun-1 and Laffa S x BAU Begun-1 were evaluated for resistance to phomopsis blight and fruit rot under confined field conditions. The inoculated plants exhibited differential disease reactions. Among the parents, BAU Begun-1 was resistant whereas Dohazari G and Laffa S were susceptible to Phomopsis vexans. All the phenotypes of F4 progenies showed resistant reaction to the disease. Significant differences were observed among the phenotypes in all the yield components. High genotypic and phenotypic coefficient of variation, heritability and per cent genetic advance were estimated for number of fruits per plant, number of secondary branch per plant, fruit length and fruit breadth. Significant positive correlation was observed between yield contributing characters. Random amplified polymorphic DNA technique was used for assessing genetic variation and relationship among parent cultivars and their F4 progenies of eggplant. Amplification with five decamer primers generated 69.0% polymorphic bands. Comparatively higher genetic distance was observed between Laffa S vs. green globose (Dohazari G x BAU Begun-1). The dendogram constructed from Neis genetic distance produced two main clusters, the parent cultivars and six F4 lines formed cluster 1 and one line in cluster 2. F4 lines of the tested phenotypes showed similar disease reaction and divided into same sub cluster. The parent cultivars were different in case of disease reaction and finally divided into two groups, susceptible cultivars Laffa S and Dohazari G belonged to group 1 and the resistant parent BAU Begun-1 formed another group. Int. J. Agril. Res. Innov. & Tech. 3 (1): 35-46, June, 2013 DOI: http://dx.doi.org/10.3329/ijarit.v3i1.16053